(untitled) (International Journal of Pharmaceutical and Life Sciences, 2013)
Nanoparticles represent a promising drug delivery system of controlled and targeted drug release. They are specially designed to release the drug in the vicinity of target tissue. The aim of this study was to prepare and evaluate polymethacrylic acid nanoparticles containing stavudine in different drug to polymer ratio by nanoprecipitation method to be 121 + 8 to 403 + 4 nm. The particle size of the nanoparticles was gradually increased with increase in the proportion of polymethacrylic acid polymer. The drug content of the nanoparticles was increasing on increasing polymer concentration up to a particular concentration. No appreciable difference was observed in the extent of degradation of product during 60 days in which, nanoparticles were stored at various temperatures. FT-IR studies indicated that there was no chemical interaction between drug and polymer and stability of drug. The in-vitro release behavior from all the drug loaded batches was found to be zero order and provided sustained release over a period of 24 h. The developed formulation overcome and alleviates the drawbacks and limitations of stavudine sustained release formulations and could possibility be advantageous in terms of increased bioavailability of stavudine. DOI: http://dx.doi.org/ International Journal of Pharmaceutical and Life Sciences Volume 2, Issue 4: October 2013; 133-140